Language, strategy, and influence: a pragmatic analysis of Indonesian YouTube influencers and their impact on social media - Indah Rahmayanti; Fathur Rokhman; Hari Bakti Mardikantoro; Rahayu Pristiwati (Cogent Arts & Humanities)
The pragmatic aspects of communication among Indonesian YouTube influencers and the people have given birth to interactive communication. This study aims to examine the function of pragmatics in Indonesian podcasts with focus on speech acts, speech strategies, politeness, and the cooperative principle to generate patterns of language strategies for Indonesian influencers. Research methodology used is pragmatic research utilizing qualitative analysis of the kind derived from Conversation Analysis (CA) that searches for meaning and function of language regarding speech acts, speech strategies, politeness, and cooperative principle. Data were gleaned from phrases of YouTube podcasters of six high-exposure Indonesian YouTubers by the names Jess No Limit, Ricis Official, Frost Diamond, Atta Halilintar, Willie Salim, and Deddy Corbuzier. The research findings reveal that Indonesian influencers use speech acts of various kinds including locutionary, illocutionary, and perlocutionary acts in a bid to achieve maximum interaction with the audience. In addition, speech strategies and politeness are used to reinforce social ties and achieve closeness with the audience. Finally, cooperative principle violative acts such as quantity, quality, relevance, and manner are used to create exciting conversation dynamics. The use of appropriate language and precise pragmatic strategies has the potential to increase audience engagement and strengthen their loyalty.